PERANAN CONTENT CREATOR DALAM MENINGKATKAN BRAND AWARENESS PADA SANGGAR KREATIVITAS BOMBI JAKARTA - Amelia; Hendro Lukman; Sriwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The development of information technology enters people's daily lives, increasing activities with growing digitalization. One model of digitization is social media which is used to communicate as well as for promotion and marketing. Social media requires content creators. Content creators are urgently needed by business owners to support them in promoting their business products, one of which is